Digital Youth, Innovation, and the Unexpected - McPherson, Tara (The MIT Press, 2007)
How emergent practices and developments in young people's digital media can result in technological innovation or lead to unintended learning experiences and unanticipated social encounters.Young people's use of digital media may result in various innovations and unexpected outcomes, from the use of videogame technologies to create films to the effect of home digital media on family life. This volume examines the core issues that arise when digital media use results in unintended learning experiences and unanticipated social encounters. The contributors examine the complex mix of emergent practices and developments online and elsewhere that empower young users to function as drivers of technological change, recognizing that these new technologies are embedded in larger social systems, school, family, friends. The chapters consider such topics as (un)equal access across economic, racial, and ethnic lines; media panics and social anxieties; policy and Internet protocols; media literacy; citizenship vs. consumption; creativity and collaboration; digital media and gender equity; shifting notions of temporality; and defining the public/private divide. ContributorsSteve Anderson, Anne Balsamo, Justine Cassell, Meg Cramer, Robert A. Heverly, Paula K Hooper, Sonia Livingstone, Henry Lowood, Robert Samuels, Christian Sandvig, Ellen Seiter, Sarita Yardi